PERAN FATWA DSN MUI DALAM MENDUKUNG REGULASI DAN PERTUMBUHAN KEUANGAN DIGITAL SYARIAH DI INDONESIA - Nisa’, Khoirun; Wiaam, Isnania; Handriyani, Heni; Sholahuddin, Muhammad (HUMAN FALAH: Jurnal Ekonomi dan Bisnis Islam, 2025)
This research analyzes various fatwas issued by the National ShariaCouncil of the Indonesian Ulema Council (DSN-MUI) related to digital finance.The main focus is on how these fatwas are implemented and their impact on thedigital finance ecosystem in Indonesia. The research method used is qualitativewith content analysis, collecting secondary data from official documents andrelated literature. The results show that the DSN-MUI fatwas on digital financeemphasize the importance of transparency, fairness, and integrity in transactions.These fatwas cover various aspects such as online buying and selling,dropshipping, technology-based financing services, and the use of electronicmoney. The implementation of these fatwas has had a positive impact onincreasing the trust of the Muslim community, the growth of the Islamic fintechecosystem, and support from regulators. However, challenges in implementationand compliance with sharia principles remain, including the need for rigoroussharia audits and improved sharia literacy among the public. This researchmakes an important contribution to the Islamic finance literature and providespractical guidance for policy makers and financial practitioners in implementingDSN-MUI fatwas more effectively.